Correlation of EFL learners’ metalinguistic knowledge and grammatical accuracy - Abdulaziz B Sanosi (Universitas Syiah Kuala, 2022)
Grammar teaching has been a topic of debate for a considerably long time. Researchers and teachers discussed the benefits and shortcomings of its explicit instruction, which entails students’ awareness of metalanguage. Although much research has investigated metalanguage, its effect on improving students’ grammatical accuracy is still an unresolved issue, and the research concerning it is relatively limited. Nevertheless, it is widely recognised that metalanguage is beneficial for grammar teaching. Responding to this research gap, the present study investigated the relationship between EFL students’ metalinguistic knowledge and their grammatical accuracy. The researcher adopted a descriptive quantitative research design where two tests were administered to undergraduate participants (n=124). The tests scores were analysed using the Blackboard item-analysis tool and SPSS software to generate statistical information regarding the participants’ scores. The study findings revealed a significant positive correlation between the scores. This correlation was moderate and occurred at the students’ overall score level. Moreover, the study revealed a proper level of metalinguistic knowledge that was not in perfect parallel with students’ grammatical accuracy. The generated findings can provide insightful implications for grammar teaching. This finding is significant for EFL teachers as it supports claims on the importance of explicit grammar instruction. It is also essential for learners as they can use metalanguage to develop their learning. Moreover, the study suggests areas that may be helpful for researchers to further explore the issue.